Magnetic phase separation in EuB6 detected by muon spin rotation - Brooks, M; Lancaster, T; Blundell, S; Hayes, W; Pratt, F; Fisk, Z (2004)
We report results of the first muon-spin rotation measurements performed on the low carrier density ferromagnet EuB6. The ferromagnetic state is reached via two magnetic transitions at Tm=15.5 K and T c=12.6 K. Two distinct components are resolved in the muon data, one oscillatory and one non-oscillatory, which arise from different types of magnetic environment, and we have followed the temperature dependence of these components in detail. These results provide evidence for magnetic phase separation and can be interpreted in terms of the gradual coalescing of magnetic polarons.